2009
DOI: 10.1007/s12663-009-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Keloidoscope: in search for the ideal treatment of keloids

Abstract: Although keloids were recognised in the Smith Papyrus of ancient times, the precise definition, cause and management have remained elusive. Several forms of treatment have been used with varying success. Objectives This study assesses and compares the value of intralesional steroid (Triamcinolone acetonide 40mg/ml), cryotherapy and cryotherapy with intralesional steroid in the treatment of keloids. Methodology 33 patients were studied, 11 each in the three arms and the volume of the keloids was recorded using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…37,40 An interindividual controlled study with 10 patients using calipers and digital photography was performed to determine the effect of cryotherapy and corticosteroid injections in keloids. 25 A more objective assessment method was used in a study of 33 patients 35 : they took a wax pattern of alginate impressions of each keloid to observe changes in volume and surface of the keloids. Patients were treated only once with either cryotherapy or corticosteroid injections alone or their combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,40 An interindividual controlled study with 10 patients using calipers and digital photography was performed to determine the effect of cryotherapy and corticosteroid injections in keloids. 25 A more objective assessment method was used in a study of 33 patients 35 : they took a wax pattern of alginate impressions of each keloid to observe changes in volume and surface of the keloids. Patients were treated only once with either cryotherapy or corticosteroid injections alone or their combination.…”
Section: Discussionmentioning
confidence: 99%
“…27,33 Although combination of cryotherapy and intralesional triamcinolone acetonide represents a frequently used technique for the treatment of keloids and has been highlighted as a promising approach in current guidelines, only 4 studies exist on its combination. 25,[34][35][36] All of them confirmed the effectiveness of intralesional corticosteroids combined with cryotherapy, but none of them applied modern objective measurement methods to assess the therapeutic success. Furthermore, treatment regimens varied, and patients were evaluated before and at the end of treatment, without information on treatment progress.…”
mentioning
confidence: 99%
“…NS, not specified. factor of 20 [6,7,10,12,[17][18][19][20][21][22] (Table 1). Whereas one study reported to inject 0.1 mL of TAC 10 mg/mL (dose: 1 mg TAC) per cm 2 of keloid [12], other studies reported to inject 0.5 mL of TAC 40 mg/mL (dose: 20 mg TAC) per cm 2 of keloid [6,18,19].…”
Section: Drugs and Dosingmentioning
confidence: 99%
“…The maximum dose administered per session was mentioned in twelve (32%) studies and varied from 20 to 80 mg (Table 1). The total number of treatment sessions varied from one [20] to eight [11,13,16], with the median being four sessions. Reported treatment intervals differed from weekly [16,23] to monthly [15,17,[24][25][26][27].…”
Section: Drugs and Dosingmentioning
confidence: 99%
See 1 more Smart Citation